Studying the selectivity of neuronal subpopulations within fMRI voxels - Sapountzis, Panagiotis (2010)
Functional magnetic resonance imaging (fMRI) has become a ubiquitous tool in cognitive neuroscience. The technique allows the non-invasive measurements of cortical responses, but only on the millimeter scale. Recently, two methods aimed at studying the selectivity of neuronal populations on a subvoxel scale. The first technique, fMRI adaptation, relies on the observation that the fMRI response in a given voxel is reduced after prolonged presentation of a stimulus, and that this reduction is selective to the characteristics of the repeated stimuli. The second technique, multi-variate pattern analysis (MVPA), makes use of multi-variate statistics to recover small biases in individual voxels. This thesis compared the two techniques with the aim of studying early- and mid-level processing in the visual cortex. Chapter 3 investigated whether adaptation and MVPA provide consistent results about the properties of the cortical areas under study. To address this question, this thesis compared the two methods for their ability to detect the well documented orientation selectivity in early visual cortex. Using optimised experimental designs for each, this thesis found that the MVPA approach was more sensitive to small differences in stimulus orientation than the adaptation paradigm. Estimates of orientation selectivity obtained with the two methods were, however, very highly correlated across visual areas. Chapters 4 and 5 used both techniques to investigate how local orientation signals are combined and detected in intermediate levels of visual processing. In both chapters the MVPA was more efficient in detecting differences between stimulus categories. In particular, chapter 4 used plaid stimuli, made of the linear sum of two sinusoidal gratings. We obtained weak but consistent evidence, pointing to the direction that V2 might play a role in Fourier component integration. Chapter 5 used contour stimuli constructed from two luminance modulated sinusoidal gratings, with different orientations. Whereas, adaptation failed to reveal contour selectivity, MVPA accuracy was high in most areas tested. However, the experiment did not reveal a significant difference between the test and control conditions. Chapter 6 investigated the encoding of spatial phase in the cortex. Phase is a fundamental aspect of spatial vision, crucial both for the extraction of local features and overall scene perception. This thesis showed that several visual areas, including the primary visual cortex, were sensitive to relative phase combinations. However, phase coherence was optimally encoded in extrastriate areas as predicted by the physiological properties of higher regions.